Development Of The USM Wind Tunnel Validation Model For Calibration - Sim, Chiow Moon (Universiti Sains Malaysia, 2018)
Wind tunnel is a device which plays the important role in the study of effect of a moving object through air stream. It generates the air flow which simulates the wind flow condition. The performance of wind tunnel is always a factor to be concerned. A good flow quality in test section can be surely reduce the uncertainty in the experiment conducted, and hence, increase the repeatability and reliability for the experimental results. Calibration of wind tunnel should be emphasized in the laboratory to maintain the flow quality in the test section. The development of a standard model for USM wind tunnel calibration is researched in current project. The standard model will need to possess a valid experimental data for a wind tunnel experiment. The main objective to be attained is to establish a standard model for the wind tunnel calibration. In current research, it is important to study the pressure distribution on the selected wing model for a range of angles of attack and then further investigate on the lift contribution for the model by integrating the pressure distribution. The obtained experimental results will be analyzed and validated by comparing with other wind tunnel data for similar model and conditions. In brief, NACA 2412 infinite wing model is researched in this FYP work. The model was pressure tapped with 33 pressure taps on upper surface and lower surface. All the instruments involved in the experiment was initially calibrated to avoid displeased uncertainty in the experiment. The experiment was conducted under incompressible flow. Pressure distribution at various angles of attack were measured and lift contribution was computed for the model. Experimental data was then validated with reference data and discrepancy on the experimental data was identified. The pressure distribution on the upper surface of the model did not reach a good agreement with reference pressure distribution for the upper surface. However, the pressure distribution of lower surface measured from experiment agreed well with reference data. The finding from discrepancy analysis experiment indicates that the discrepancy might cause by the deterioration of the pressure taps at the inner assembly of the model which it can’t be checked due to the disassemble design of model. Further recommendations are also given based on the improvement on the model accuracy measurement, qualitative measurement and validation method for future research.